Isometamidium chloride and homidium chloride fail to cure mice infected with Ethiopian Trypanosoma evansi type A and B - Mekonnen, Gebrekrustos; Mohammed, Elmi Fahiye; Kidane, Weldu; Nesibu, Awol; Yohannes, Hagos; Van Reet, Nick; Büscher, Philippe; Birhanu, Hadush (PLOS Neglected Tropical Diseases, 2018)
Author summary Surra is a vector borne disease in camels, horses, water buffaloes, cattle and other domestic animals caused by Trypanosoma (T.) evansi. This protozoan parasite is transmitted by biting flies such as tabanids and stable flies and is endemic in many countries in Northern and Eastern Africa, Latin America and Asia. Surra is responsible for high economic losses due to mortality and morbidity of draught animals and leads to animal trade restrictions in endemic regions. Control of surra is mainly based on the treatment of sick animals presenting clinical symptoms. In Ethiopia two different types of T. evansi (A and B) have been described, yet no data existed about the drug sensitivity of any T. evansi type. In this study, we show for the first time that T. evansi type B is naturally in vivo resistant to the phenanthridine class of trypanocidal drugs, a phenonomen that was previously described for T. evansi type A. All Ethiopian T. evansi types are sensitive to melarsamine hydrochloride and diminazene diaceturate. Unfortunately, the most efficacious drugs are either not registered in Ethiopia or escape quality control of the active substance in commercial drug formulations. Furthermore, the inefficacious drugs remain accessible on the market despite their toxicity for animals.